2006
DOI: 10.1007/s11085-006-9003-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Silicon on the Oxidation Behavior of Ni-Base Chromia-Forming Alloys

Abstract: This paper compares and analyzes the oxidation behavior of Ni-base alloyswith and without about 2.7 wt.% Si addition. The Ni-base alloys studied were of two types: cast model alloys or wrought commercial alloys. Oxidation testing was conducted at 1000 • C in still air. The specific aspects studied were scale spallation resistance, nature by which the silicon oxidized, and the influence of silicon on the subsurface depletion behavior of chromium. From oxidation results of the cast model alloys, Si addition was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(43 citation statements)
references
References 27 publications
2
30
0
Order By: Relevance
“…According to the classical diffusion theory of internal oxidation, as expressed in Eqs. (8) and (9), the rate of penetration is decreased as N Si increases. However, alloy A1 with its higher silicon content, oxidises to greater depths than does the low silicon alloy A2.…”
Section: Oxidationmentioning
confidence: 97%
See 1 more Smart Citation
“…According to the classical diffusion theory of internal oxidation, as expressed in Eqs. (8) and (9), the rate of penetration is decreased as N Si increases. However, alloy A1 with its higher silicon content, oxidises to greater depths than does the low silicon alloy A2.…”
Section: Oxidationmentioning
confidence: 97%
“…Its compositional specification is seen in Table 1 to be quite wide, particularly with respect to minority alloy constituents. It is known [8,9] that changing the concentration of manganese and silicon in wrought alloys can alter their oxidation rates considerably. Commercial alloys conforming to the HP40Nb specification can differ significantly in composition, and the aim of the present work was to determine whether these variations would affect corrosion resistance under simulated service conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The 400 hours time of oxidation was long enough for diffusion processes which resulted with the change of the scale composition and probably little amount of CoO or CoCr 2 O 4 spinel structure was formed. This scale composition was typical for cobalt chromium alloys which were at least contaminated with silicon and if 0,05 weight percent silicon was added to the Co-25Cr-1.0C alloy, then parabolic oxidation rates two orders of magnitude lower were recorded [9,10] It was concluded that silicon has its effect at the alloy surface by promoting Cr 2 O 3 formation [11,12]. This behavior of silicon was also indicated by chemical composition of the region just under the scale (Fig.5) and increase of its amount.…”
Section: Resultsmentioning
confidence: 81%
“…The former was inferred to be SiO 2 . Addition of Si is known to improve the oxidation resistance of chromia-forming alloys [10][11][12]; however, it is also known to decrease scale spallation resistance [12][13][14]. Apparently, the nominally 2.75 wt% Si addition in the HR-160 alloy forms a continuous SiO 2 layer at the chromia/alloy interface and this in turn may have considerably decreased scale adhesion particularly at 982 o C. It is seen from Table III that HR-160 alloy underwent considerable metal loss (~ 43 µm) at 982 o C even though it contains sufficient amount of Cr to establish a protective oxide scale.…”
Section: Resultsmentioning
confidence: 99%
“…The HR-160 alloy showed the highest interfacial Cr content compared to 230 and HR-120 alloys. Indeed, Li and Gleeson [12] showed the beneficial effect of Si addition (2.75 wt%) in improving the interfacial Cr content in Ni-Cr-Co alloy system. However, it should be noted that 8 wt% is still insufficient to establish a continuous Cr 2 O 3 scale on a bare alloy, and once initial breakdown occurs in HR-160 alloy, it becomes susceptible to a rapid internal oxidation because of its relatively high Si content.…”
Section: Hr-120mentioning
confidence: 99%